О норме разложимых подгрупп в непериодических группах - Лиман, Ф.Н.; Лукашова, Т.Д. (Український математичний журнал, 2015)
Розглядаються взаємозв’язки мiж властивостями неперiодичнихгр уп та їхнор м розкладнихпiдгр уп. Зокрема, дослiджено вплив обмежень, якi задовольняє норма розкладнихпiдгр уп, на властивостi самої групи за умови, що така норма недедекiндова. Описано будову неперiодичнихлок ально нiльпотентнихгр уп, у якихвк азана норма є недедекiндовою. Окрiм того, встановлено деякi зв’язки мiж нормою абелевихнециклiчнихт а нормою розкладних пiдгруп. We study the relations between the properties of nonperiodic groups and their norms of decomposable subgroups. In particular, we analyze the influence of restrictions imposed on the norm of decomposable subgroups on the properties of the group provided that this norm is non-Dedekind. We also describe the structure of nonperiodic locally nilpotent groups for which the indicated norm is non-Dedekind. Furthermore, some relations between the norm of noncyclic Abelian subgroups and the norm of decomposable subgroups are established.